Development of Science Digital Scrapbook as Authentic Assessment to Measure Learning Outcome of Junior High School Students - Agung Laksono; Arif Widiyatmoko* (Universitas Syiah Kuala, 2022)
Learning during the COVID-19 pandemic has an impact on students’ learning outcomes. Observation results in SMP 2 Dawe Kudus showed that students’ learning outcomes in science subjects are still low. This school was chosen because of the location of the school in remote areas which resulted in not optimal use of digital devices for assessment in learning. The purpose of this study is to analyze the characteristics, feasibility, and profile of learning outcomes using digital science scrapbooks as authentic assessment to measure the learning outcomes of junior high school students on the theme of Additives and Addictive Substances. This study used a Research and Development (RD) design with ADDIE model. The science digital scrapbook as an authentic assessment developed in this study was declared feasible to use based on the assessment of material experts and evaluations. The reliability coefficient values obtained from small-scale tests for essay questions, attitude assessment instruments, and skills assessment instruments were obtained 0.62; 0.84; and 0.38. Students’ learning outcomes measured using a digital science scrapbook as an authentic assessment showed 83.3% of students were complete in the realm of knowledge, 100% completed in the realm of attitudes, and 100% completed in the realm of skills. The conclusion of this study is science digital scrapbook as an authentic assessment developed in this study was feasible to be used to measure the learning outcomes of junior high school students on additives and addictive substances concept